(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The term "artistic" is derived from the Arabic words "bad’un" and "bade’a" - meaning to innovate, create, create, invent, discover. This term refers to the most primary, leading concept of art forms that follow the laws of beauty.